A STUDY ON COMMUNITY EMPOWERMENT FOR MENTAL HEALTH EDUCATION IN KLEAK VILLAGE, MANADO CITY, NORTH SULAWESI PROVINCE - Katuuk, Deitje A.; Lengkong, Jeffry S.J.; Usoh, Elni J.; Kalalo, Debie K.R; Lolong, Rima F.; Koessoy, Herman M. (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
This study aims to empower the community to detect mental disorders early in their environment. Through counseling and training, it will provide knowledge to the community about the early signs of mental disorders and how to identify them. The method used in this study is a descriptive research method with a qualitative approach. The focus of this study is community empowerment for mental health education. In this research, the location chosen is Kleak Village in Malalayang sub-district, Manado City, North Sulawesi, Indonesia. Community empowerment for mental health education in Kleak Village, Manado City, emphasizes a holistic approach with a focus on mental health education, active community participation, self-help, networking, and advocacy. Mental disorders are closely related to mental health, including conditions such as anxiety, bipolar, depression, eating disorders, delusions, schizophrenia and anxiety disorders. Causal factors involve family issues, genetics, drugs, and stress. The healing process varies depending on the patient's condition, involving consultation with a psychiatrist and admission to a psychiatric hospital. The role of the family is very important in the treatment of patients with mental disorders, supported by health workers such as doctors and psychiatric nurses. Mental health socialization in the community is needed to increase understanding of mental health disorders. Prevention involves regular medication, increased spirituality, quality mental health services, and community understanding. The government is expected to pay serious attention by providing facilities such as mental hospitals and increasing health programs that support mental health control both in agencies and at the community level.